Melatonin Treatment During Chronic Hypoxic Gestation Improves Neonatal Cerebrovascular Function - Navarrete-Rosales, A (Elsevier Inc., 2022)
Background: Fetal chronic hypoxia is associated with blood flow redistribution and oxidative damage in the brain, leading to increased perinatal morbimortality. Melatonin reduces oxidative stress, improves vascular function, and has neuroprotective effects. Objectives: This study aimed to determine the effects of an oral melatonin treatment to pregnant ewes at high-altitude, on the cerebrovascular function of their neonates. Study design: Ten high-altitude pregnant sheep received either vehicle or melatonin (10 mg/d) during the last third of gestation until delivery. Postnatal daily hemodynamic measurements were recorded from lambs until 12 days old. In addition, lambs were submitted to a graded oxygenation protocol to assess cerebrovascular responses. Subsequently, lambs were euthanized, and middle cerebral arteries (MCA) were collected for vascular function, protein levels, and morphostructural analyses. Results: Antenatal treatment doubled plasma levels of melatonin in pregnant ewes. Melatonin increased carotid flow and decreased carotid vascular resistance in the lambs by the end of the first week. Furthermore, melatonin increased MCA s maximal vasoconstrictor and vasodilator responses, associated with nitric oxide-dependent and independent mechanisms. Conclusions: An oral treatment with melatonin during pregnancy promotes postnatal cerebral perfusion in chronically hypoxic neonates. Melatonin is a potential treatment for cerebrovascular dysfunction due to perinatal chronic hypoxia. © 2022